Strategic Philanthropists: Who Are They and Do They Matter? - Barham, Vicky; Devlin, Rose Anne; Owusu, Rebekah (Université d'Ottawa | University of Ottawa, 2017)
Anecdotal evidence suggests that charitable givers – particularly those with the financial means and inclination to make substantial donations – are increasingly strategic in their philanthropic behavior. This study is the first econometric investigation of individual strategic giving, that is giving which is planned, concentrated, and where the donor is also involved as a volunteer. Approximately 3% of the total giver population gives strategically in Canada. We find that the propensity to give strategically is strongly and positively correlated with the level of education and youth experiences, and that strategic givers are substantially more generous than non-strategic givers, particularly after controlling for endogeneity. Strategic giving has a large positive impact on the amount donated to secular organisations, but has no effect whatsoever on the level of religious giving, supporting the view that religious gifts should be modelled differently from non-religious gifts.
Keywords: strategic giving; philanthropy; charitable donations